German economy between lockdowns and normality - Claus Michelsen; Paul Berenberg-Gossler; Marius Clemens; Max Hanisch; Simon Junker; Konstantin Kholodilin; Laura Pagenhardt (DIW Weekly Report, 2021)
By lifting lockdown measures as coronavirus case numbers are rising and the vaccine rollout is proceeding slowly, the German economy is being sent on a stop-go course. Re-opening measures will probably be followed by renewed closures, at least regionally, in order to keep the spread of COVID-19 under control. Nevertheless, industry is robust overall, primarily due to good foreign business. In the service sectors, however, recovery will be sluggish following another setback at the beginning of 2021. It is likely that social and economic restrictions will only be able to be sustainably lifted over the course of the third quarter of 2021. Whereas economic output growth of 5.3 percent in 2021 still seemed realistic in December 2020, the current forecast is now projecting a significantly lower figure of 3.0 percent. Currently, growth of 3.8 percent is expected for 2022. The long-term economic consequences of the coronavirus pandemic are still unclear: For example, the extent of corporate insolvencies will not become apparent until later in 2021 at the earliest.
Keywords: E32; E66; F01; 330; business cycle forecast; economic outlook